Surface Quality Evaluation in the Milling Process Using a Ball Nose End Mill - Ján Varga; Peter Ižol; Marek Vrabeľ; Ľuboš Kaščák; Mário Drbúl; Jozef Brindza (Applied Sciences, 2023)
Shaped surfaces are increasingly used in the field of mold-making for casting or injection molding, where future products include shapes with different curvatures. These are surfaces that form convex curves, concave curves, or a combination thereof. Given these machined surfaces, it is important to know the impact of the finishing strategies on these surfaces. This paper deals with the comparison of finishing milling strategies in the production of shaped surfaces and the analysis of different methods for the evaluation of surface topography. In addition, the experimental results evaluate the roughness of the machined surface and surface shape variations. The material used for the experiments was AlCu4Mg aluminum alloy, and Constant Z, spiral and spiral circle strategies were chosen for the finishing strategies. The evaluation of surface topography and surface roughness was carried out at three different specimen heights with respect to the tool’s contact with the machined surface.